From source to tap : a case study of organic contaminants in raw and drinking water in the region of Uppsala, Sweden - Klöckner, Philipp (SLU/Dept. of Aquatic Sciences and Assessment, 2015)
In this study, water samples from the surroundings of Uppsala were examined for residues of pesticides, pharmaceuticals and other contaminants characteristic for human fecal contamination. The aim was to perform a screening of water samples to investigate the level of pollution with the mentioned compound groups. Samples were taken from upstream and downstream river water, lake water, a drinking water treatment plant and treated drinking water. The contaminants were extracted from water samples with two different solid phase extraction (SPE) cartridges. Identification and quantification was achieved via separation with ultra-performance liquid chromatography (UPLC) followed by positive and negative electrospray ionization (ESI) coupled to a high-resolution time-of-flight (TOF) mass spectrometer. Out of 17 analyzed contaminants, 9 could be detected in environmental samples of which 5 were detected in finished drinking water. None of the targeted pesticides were found in environmental samples or drinking water. The average method recovery was 51% and 39% depending on the extraction method. The limit of quantification (LOQ) ranged from 0.07 ng L-1 up to 74 ng L-1. Contaminant concentrations in environmental samples ranged from 0.55 ng L-1 to 40 ng L-1 and in drinking water from 0.22 ng L-1 to 8.0 ng L-1. Compounds detected were atenolol, benzoylecgonine, bezafibrate, caffeine, carbamazepine, co-tinine, diclofenac, metoprolol and nicotine. Compounds not detected were atrazine, cyanazine, isoproturon, ketoprofen, monensin, quinmerac and simazine. The results show that several of the target analytes were present in the environment and in drinking water at low but measurable concentrations, which shows that the drinking water treatment plant is not able to successfully remove the contaminants with conventional treatment techniques. A pilot plant with membrane technology is ineffective as well, except when coupled to granular activated carbon (GAC). Risk quotients were determined and revealed that no hazards for human health or aquatic organisms can be expected from the detected contaminant concentrations.